A geochemical and sedimentological perspective of the life cycle of Neapolis harbor (Naples, southern Italy). (15th October 2016) - Delile, H.; Goiran, J.-P.; Blichert-Toft, J.; Arnaud-Godet, F.; Romano, P.; Bravard, J.-P.
Abstract: Since the discovery of the ancient harbor of Naples in 2004 during construction work on an underground railway, geoarchaeological studies undertaken on the archaeological excavation have revealed the main stratigraphic and paleo-environmental levels of the harbor site near the Piazza Municipio. However, knowledge of the dynamics and paleo-environmental changes in the water column of the harbor, as well as the processes of transport and deposition of sediments that led to siltation and infilling of the harbor basin, has been lacking due to the absence of high-resolution data. To fill these gaps, we have undertaken a three-dimensional study (longitudinal, transverse and vertical) of the harbor deposits by carrying out geochemical and sedimentological analyses of four stratigraphic sections of the archaeological excavation. The results show that after a phase of relative calm during the first half of the 1st c. AD, siltation of the harbor progressed exponentially up to the 5th c. AD, when dredging operations were carried out to obtain a water level sufficient for the development of maritime and harbor activities. We attribute this acceleration of siltation to a combination of climatic, anthropic and volcanic factors. Volcanic activity was responsible for a high-energy, tsunami-type event during the eruption of Vesuvius in 79 AD. From the 5th c. AD onwards, the harbor basin of Neapolis does not appear to have been functional as evidenced by its transformation into a lagoon following coastal progradation. The last stage of infilling was the development of a flood-dominated fan delta under the combined influences of climatic cooling in the Early Medieval Cool Period and agro-pastoral activities in the catchment area of the harbor. Several generations of paleo-channels, containing flash flood deposits, as well as sheet wash from sheet floods, are indicative of high environmental instability in this period. Highlight: Harbor basin infilling was sensitive to climate, human land use and volcanic activity. Authigenic, detritic, biogenic, siliciclastic and carbonate fluxes were identified. A moderate tsunami has been triggered by the AD 79 Somma-Vesuvius eruption. A second dredging operation occurred during the 3rd and 5th centuries. A flood-dominated fan-delta was shaped on the harbor area during the 6th c.